Охорона і збереження культурної спадщини в просторі етнічної ідентифікації: тенденції 1990 – 2000- х рр. - Пекарчук, В. (Сiверянський лiтопис, 2015)
У статті на основі архівних та статистичних матеріалів, аналітичних напрацювань попередників розглянуто місце і роль культурної спадщини етноменшин України у процесі їхньої етнічної ідентифікації, гармонізації міжетнічних відносин. Значну увагу приділено діяльності заповідників, які були створені з метою охорони та вивчення культурної спадщини етноменшин. В статье на основе архивных и статистических материалов, аналитических наработок предшественников рассмотрены место и роль культурного наследия этнических меньшинств Украины в процессе их этнической идентификации, гармонизации межэтнических отношений. Значительное внимание уделено деятельности заповедников, которые были созданы с целью охраны и изучения культурного наследия этнических меньшинств. The article is based on archival, statistical and analytical developments predecessors The place and role of cultural heritage etnomenshyn in the process of ethnic identification harmonization of interethnic relations. The literature which includes problems of cultural heritage of the Ukrainian people only partially considers the problem areas, shapes, nature protection and preservation of the history and culture of ethnic minorities it. The importance of the described problem is determined, first of all need to have a clear idea of how the solution of an independent state interethnic relations. It was shown that Ukraine was formed and operated an extensive network of monument protection case, which relied on an appropriate legal framework, international treaty obligations, etc.. Take into account the factor of continuity and perspective in the protection and preservation of cultural heritage etnomenshyn. Much attention is given to ascertain the cause of the slow resolution of conservation issues, if not often prevent destruction and the destruction of cultural monument.